Kvalitet usluga u železničkom saobraćaju država EZ, EFTA i SFRJ - Janić, Milan; Grubor, Dmitar (Promet - Traffic&Transportation, 2012)
This paper deals with the quality of transport services in passenger and freight rail transport of the EC, EFTA and Yugoslavia. For passenger transport services the respective level has been reviewed on the system of IC-lines while for the freight transport services it has been reviewed on the system of direct freight trains. For passenger transport services the frequencies and commercial speeds have been analyzed while for freight transport services the average commercial speed has been reviewed. The author puts forth recommendations for the increase of commercial speeds.